Maternal and perinatal outcome in preterm premature rupture of membranes - M. V., Jameela Diraviyam; karunakaran, Lalithambica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm premature rupture of membranes (PPROM) occurs in 3% of pregnancies and is responsible for approximately one third of all preterm births. Objective of present study was to analyse the maternal and perinatal outcome of PPROM patients between 28 to 36 weeks +6days Methods: A descriptive study was conducted on 141 antenatal patients between 28 to 36weeks+6days with PPROM admitted to Department of Obstetrics and Gynecology, Government TD Medical College, Alappuzha, Kerala, India from September 2014 to September 2015. After establishing the diagnosis of PPROM patients were monitored and Maternal and perinatal outcomes were studied. Results: 77% patients had late PPROM. 60% of early PPROM latency period >24 hrs and were managed conservatively till 34 weeks. 18% had chorioamnionitis and immediate termination of pregnancy. 73% of newborns in this group needed admission due to complications of prematurity like RDS (54.54%). Perinatal mortality (2.12%) was due to sepsis. 80% of late PPROM had latency period <24 hrs and only 4% had chorioamnionitis.18.5% babies in this group had hyperbilirubinemia. There was statistically significant association between latency period and perinatal complications (p=0.001). RDS was 33% in latency period <24hrs, 18% in >24hrs and sepsis was 36% in >24hrs and 10% in <24hrs. Conclusions: The most common cause of perinatal mortality in early PPROM is prematurity and its complications. Hence conservative management to prolong pregnancy is recommended under strict monitoring for evidence of chorioamnionitis. At the earliest evidence of chorioamnionitis termination irrespective of gestational age is warranted. In late PPROM, perinatal outcome is good. So, termination is advised as conservative management shall add to the fetal and maternal morbidity due to sepsis.